Pengaruh GCG terhadap Kinerja Keuangan dengan CSR sebagai Pemoderasi di Perusahaan Pertambangan - Ivana Nina Esterlin Barus (Jurnal Manajemen dan Keuangan, 2016)
The mining company’s financial performance period 2010-2012 fluctuated. It is certainly influenced by many factors, such as good corporate governance. In addition, there is a moderating factor of corporate social responsibility. This study aims to investigate the influence of good corporate governance to the mining company’s financial performance, examining the influence of corporate social responsibility to the mining company’s financial performance and investigated the influence of corporate social responsibility to the mining company’s financial performance and examine whether corporate social responsibility as a moderating. The study population was a mining company listed on the Indonesia Stock Exchange, with a total sample of 51 data. The research data sourced from the documentation of financial statements published by the BEI and IICG survei results. The research model is a regression to the moderated regression analysis (MRA). The results of this study indicate that good corporate governance is partially not affect the Company’s financial performance Mining. But corporate social responsibility partially affect the Company’s financial performance Mining. Corporate social responsibility is not a moderating variable between good corporate governance and financial performance Mining Company. Research capabilities regression model can explain the variation of variable financial performance of 4.6%.